Citywide quantification of street-canyon contributions to near-road NO2 in Hong Kong using a coupled WRF-CMAQ-ADMS framework - Zejiang Yu; Peihan Wang; Jenny Stocker; Kate Johnson; Brian Bien; Jimmy Chi Hung Fung (Environmental Pollution, 2026)

Evaluating satellite and modeled lake surface water temperature across the contiguous United States - Blake A. Schaeffer; Hannah Ferriby; Wilson Salls; Natalie Reynolds; Jeffrey W. Hollister; Betty Kreakie; Stephen Shivers; Brent Johnson; Olivia Cronin-Golomb; Kate Meyers; Maxwell Beal (Hydrobiologia, 2026)

Leaf Size in Conifers: Global Associations With Climate and Evolutionary History - Katya I. Bandow; Timothy J. Brodribb; Benjamin Halliwell; Matilda J. M. Brown; Kate M. Johnson; Gregory J. Jordan (Global Change Biology, 2026)
Global analyses of leaf size suggest that large leaves predominate in favourably warm and wet climates, and small leaves occur at climatic extremes. However, these patterns are dominated by data from angiosperms and may obscure drivers of leaf size variation in older, less speciose groups, such as conifers. Here we employ a novel modelling framework, multi‐response phylogenetic mixed models (MRPMM), that identifies trait correlations at both phylogenetic and phylogenetically independent levels to investigate how climate influences leaf size evolution across conifers. We show overall patterns for all conifers and focus on three groups with distinctive leaf architectures: scale‐leaved Cupressaceae, needle‐leaved Pinus and broad‐leaved Podocarpus . We found moderate to strong phylogenetic signal in conifer leaf and climate niche traits. Phylogenetic relationships explained most of the association between leaf size and climate, with temperature revealed as a stronger driver than dry season precipitation, indicating deep‐time co‐evolutionary associations. These patterns reflect trade‐offs associated with leaf hydraulic architecture under contrasting selection pressures. In single‐veined leaves, lateral water transport and thus leaf width is constrained, yet this narrow leaf form can be advantageous for survival under climatic extremes such as drought and freezing. In contrast, anatomical innovations (like accessory transfusion tissue in Podocarpus ) allow for broader leaves which are favourable in competitive environments, while also potentially making leaves more vulnerable to climate extremes. Our results support previous evidence for phylogenetic niche conservatism in conifers, where species tend to track their ancestral climatic preferences rather than adapting to new environments. This conservatism, likely controlled by leaf hydraulic architecture, results in strong evolutionary constraints on current bioclimatic distributions and potential responses to changing climates in conifers. This study also highlights the importance of considering phylogenetic impacts on functional trait evolution, especially in evolutionarily conservative groups like conifers.

Higher alkalinity increases copper toxicity in phytoplankton: The importance of pH flux when treating algal blooms - Anna C. Mollica; Megan T. Wesche; Matthew F. Gladfelter; Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Kate L. Merrill; Alan E. Wilson (Harmful Algae, 2026)

Modeling of gene regulatory networks: an annotated glossary - Avilash Singh Yadav; Nicholas J. Russell; Adriana I. Hernández; Alaina R. Petlewski; Arielle R. Johnson; Ayress D. Grinage; Barituziga Banuna; Clarice J. Guan; Elizabeth H. Mahood; Gordon C. Younkin; Hannah R. Thomas; Heather R. Phillips; et al. (Trends in Plant Science, 2026)

Zebrafish parental co-exposure to environmentally relevant levels of inorganic arsenic + methylmercury impacts neurobehavior in parents and progeny - Sarah E. Rothenberg; Eric Johnson; Jane LaDu; Lindsey St. Mary; Jay C. Adams; Kate Rice; Brian P. Jackson; Robyn L. Tanguay; Lisa Truong (Environmental Toxicology and Pharmacology, 2026)

A scoping review on the impact of ambient temperature on human infertility - Seulkee Heo; Garam Byun; Yongsoo Choi; Yimeng Song; Mercedes Bravo; Tian Ma; Rory Stewart; Audrey Amezcua-Smith; Ji-Young Son; Leo Goldsmith; Kate Burrows; Hayon Michelle Choi; et al. (Environmental Research, 2026)

Playing dice with behavior: drivers of stochastic individuality - Jacob Johnson; Kirsten Sheehy; Kate L. Laskowski (Trends in Ecology & Evolution, 2026)

Repeated low-dose copper algaecide treatments promote beneficial phytoplankton and zooplankton communities - Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Journal of Environmental Management, 2025)

A Mutation in Damage-Specific DNA Binding Protein One (ddb-1) Underlies the Phenotype of the No-Marginal-Zone (nmz) Mutant Zebrafish - Kailey Jerome; Aria Gish; Taylor Aakre; Taylor Brend; Mara Kate Grenier; Christina L. Johnson; Jaxon Gronneberg; Colin K. O’Neill; Lucas Radermacher; Tristan Darland (Fishes, 2025)
The ciliary marginal zone (CMZ) is a region in the peripheral-most retina that displays ongoing retinogenesis during growth and expansion of the eye in adulthood. While there is evidence that this capacity also exists in birds and mammals, it is far more robust in fish and amphibians. The process of CMZ retinogenesis is essentially equivalent to that seen early in the central retina; however, its regulation is not fully understood. In a previous study, we attempted to uncover novel regulatory genes by using a forward genetics screen in zebrafish, looking for recessive CMZ mutants. One of the mutants found was called no marginal zone (nmz). The nmz mutant showed relatively normal central retina development, but a lack of cells in the CMZ by 5 days post fertilization (dpf). Mapping, genomic sequencing, and complementation analysis using a second mutant line (m863) isolated in another laboratory showed that a mutation in damage-specific DNA binding protein-1 (ddb-1) gene underlies the phenotype seen in nmz. BrdU labeling suggested that later expansion and differentiation of CMZ retinal progenitors is more affected by ddb-1 loss than the earlier process of stem cell asymmetric division. As was seen for the m863 mutant and in other studies with mice, one profound effect of ddb-1 loss in nmz was the upregulation in expression of tp53 and several of its downstream effectors. Several important genes important in CMZ retinogenesis are also downregulated in the nmz mutant. The change in gene expression would suggest that ddb-1 loss leads to increased cell cycle disruption and apoptosis at the expense of CMZ retinogenesis. While homozygosity is lethal, heterozygous fish appear to be completely normal in morphology, visual function, and behavior.

Modelling temperature variations in Birmingham, UK at the neighbourhood scale: Using ADMS-Urban climate model - Jian Zhong; Yanzhi Lu; Jenny Stocker; Victoria Hamilton; Kate Johnson (Sustainable Cities and Society, 2025)

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

Mapping the impact of age and APOE risk factors for late onset Alzheimer’s disease on long range brain connections through multiscale bundle analysis - Jacques Stout; Robert J. Anderson; Ali Mahzarnia; Zay Yar Han; Kate Beck; Jeffrey Browndyke; Kim Johnson; Richard J. O’Brien; Alexandra Badea (Brain Structure and Function, 2025)

Evaluating the tolerance of harmful algal bloom communities to copper - Ashley V. Hennessey; Michael B. McDonald; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Environmental Pollution, 2025)

Temperature and leaf form drive contrasting sensitivity to nitrogen deposition across European forests - Helena Vallicrosa; Kate M. Johnson; Arthur Gessler; Sophia Etzold; Marco Ferretti; Peter Waldner; Charlotte Grossiord (Science of The Total Environment, 2024)

Modelling the influence of road elevation on pollutant dispersion - James O’Neill; Martin Seaton; Kate Johnson; Jenny Stocker; Rohan Patel; Martine Van Poppel; David Carruthers (Air Quality, Atmosphere & Health, 2024)

“It’s a little soap opera of its own”: Fascinating green roofs offer complexity, movement, sensory engagement, and vast vistas - Kate Lee; Belinda Wylie; Nicholas S.G. Williams; Katherine A. Johnson; Leisa D. Sargent; Kathryn J.H. Williams (Landscape and Urban Planning, 2024)

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

The ethics of intervening in animal behaviour for conservation - Thom van Dooren; Catherine J. Price; Peter B. Banks; Oded Berger-Tal; Matthew Chrulew; Jane Johnson; Gabrielle Lajeunesse; Kate E. Lynch; Clare McArthur; Finn C.G. Parker; Myles Oakey; Benjamin J. Pitcher; et al. (Trends in Ecology & Evolution, 2023)

Convection-permitting climate simulations for South America with the Met Office Unified Model - Kate Halladay; Ron Kahana; Ben Johnson; Christopher Still; Giorgia Fosser; Lincoln Alves (Climate Dynamics, 2023)
We present the first convection-permitting regional climate model (CPRCM) simulations at 4.5 km horizontal resolution for South America at near-continental scale, including full details of the experimental setup and results from the reanalysis-driven hindcast and climate model-driven present-day simulations. We use a range of satellite and ground-based observations to evaluate the CPRCM simulations covering the period 1998–2007 comparing the CPRCM output with lower resolution regional and global climate model configurations for key regions of Brazil. We find that using the convection-permitting model at high resolution leads to large improvements in the representation of precipitation, specifically in simulating its diurnal cycle, frequency, and sub-daily intensity distribution (i.e. the proportion of heavy and light precipitation). We tentatively conclude that there are also improvements in the spatial structure of precipitation. We see higher precipitation intensity and extremes over Amazonia in the CPRCMs compared with observations, though more sub-daily observational data from meteorological stations are required to conclusively determine whether the CPRCMs add value in this regard. For annual mean precipitation and mean, maximum and minimum near surface temperatures, it is not clear that the CPRCMs add value compared with coarser-resolution models with parameterised convection. We also find large changes in the contribution to evapotranspiration from canopy evaporation compared to soil evaporation and transpiration compared with the RCM. This is likely to be related to the shift in precipitation intensity distribution of the CPRCMs compared to the RCM and its impact on the hydrological requires further investigation.

Phylogenetic, species richness and logistic influences on the biodiscovery process in Cnidaria - Mark P. Johnson; Bill J. Baker; Ellie-Ann Conneely; Kate McKeever; Ryan M. Young; Claire Laguionie-Marchais; A. Louise Allcock (Frontiers in Marine Science, 2022)
The extent to which any particular taxon supplies novel natural products depends on biological and evolutionary differences, and on decisions made by (or constraints on) biodiscovery scientists. The influences of different sources of variability on the biodiscovery process were examined in a study of the Cnidaria, a group recognised as an important source of novel marine natural products. The number of species with at least one novel metabolite within a genus was related to the number of species in the genus. This pattern implies that different genera do not differ in the probability of containing a species with novel natural products. Outlying points of this relationship were consistent with the ease of obtaining material through culturing organisms. The most productive five species were the sources of over 100 novel metabolites each. The distribution of novel metabolites across species showed no signs of exhausting novelty for the most productive source species. Novel metabolite drug likeness (ADMET-score) varied among genera. However, this pattern of variation was of the same degree as observed for molecular weights of metabolites, suggesting that differences among genera are generated by the decisions of analysts with different interests and do not reflect underlying biology. Biogeographic patterns of soft coral species with novel natural products were matched to regional species richness. Overall, the evidence for phylogenetic or spatial influences on the chance of finding novel metabolites was weak. The patterns are consistent with a constant chance of finding novel natural products across different species, with some constraints linked to ease of sampling or culturing and some reinforcement of biodiscovery in species that have previously been the source of novel metabolites.

A possible role for river restoration enhancing biodiversity through interaction with wildfire - Brittany E. Pugh; Megan Colley; Stephen J. Dugdale; Patrick Edwards; Rebecca Flitcroft; Andrés Holz; Matthew Johnson; Michela Mariani; Mickey Means‐Brous; Kate Meyer; Kevan B. Moffett; Lisa Renan; et al. (Global Ecology and Biogeography, 2022)
Background Historically, wildfire regimes produced important landscape‐scale disturbances in many regions globally. The “pyrodiversity begets biodiversity” hypothesis suggests that wildfires that generate temporally and spatially heterogeneous mosaics of wildfire severity and post‐burn recovery enhance biodiversity at landscape scales. However, river management has often led to channel incision that disconnects rivers from their floodplains, desiccating floodplain habitats and depleting groundwater. In conjunction with predicted increases in frequency, intensity and extent of wildfires under climate change, this increases the likelihood of deep, uniform burns that reduce biodiversity. Predicted synergy of river restoration and biodiversity increase Recent focus on floodplain re‐wetting and restoration of successional floodplain habitat mosaics, developed for river management and flood prevention, could reduce wildfire intensity in restored floodplains and make the burns less uniform, increasing climate‐change resilience; an important synergy. According to theory, this would also enhance biodiversity. However, this possibility is yet to be tested empirically. We suggest potential research avenues. Illustration and future directions We illustrate the interaction between wildfire and river restoration using a restoration project in Oregon, USA. A project to reconnect the South Fork McKenzie River and its floodplain suffered a major burn (“Holiday Farm” wildfire, 2020), offering a rare opportunity to study the interaction between this type of river restoration and wildfire; specifically, the predicted increases in pyrodiversity and biodiversity. Given the importance of river and wetland ecosystems for biodiversity globally, a research priority should be to increase our understanding of potential mechanisms for a “triple win” of flood reduction, wildfire alleviation and biodiversity promotion.

A Review of Northern Fur Seal (Callorhinus ursinus) Literature to Direct Future Health Monitoring Initiatives - Valerie Cortés; Kelly Patyk; Claire Simeone; Valerie Johnson; Johanna Vega; Kate Savage; Colleen Duncan (Oceans, 2022)
Northern fur seals (Callorhinus ursinus, NFS) are a vulnerable species broadly distributed throughout the north Pacific. Although commercial hunting stopped in 1984, the population has continued to decline for unknown reasons. The goal of this scoping review was to synthesize and review 50 years of literature relevant to the health of NFS to inform the development of health surveillance recommendations. Search criteria were developed and applied to three databases, followed by title and abstract screening and full text review. Articles published between 1 January 1972 and 31 December 2021 were included. Articles were categorized by health determinant, and further as relating to ten subcategories of disease. Data were summarized descriptively. A total of 148 publications met the criteria for inclusion. Infectious disease reports were common, primarily relating to metazoan parasite presence. The presence of zoonotic pathogens such as Coxiella burnetii and Brucella spp. is of public health interest, although a failure to link disease research to individual animal or population health outcomes was consistent across the literature. A shift away from the single agent focus of disease programs toward more holistic, health-oriented perspectives will require broader interdisciplinary collaboration. These findings can inform stakeholders and help them to prioritize and strategize on future NFS health research efforts.

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Regulation of host‐infection ability in the grass‐symbiotic fungus Epichloë festucae by histone H3K9 and H3K36 methyltransferases - Yonathan Lukito; Kate Lee; Nazanin Noorifar; Kimberly A. Green; David J. Winter; Arvina Ram; Tracy K. Hale; Tetsuya Chujo; Murray P. Cox; Linda J. Johnson; Barry Scott (Environmental Microbiology, 2021)
Summary Recent studies have identified key genes that control the symbiotic interaction between Epichloë festucae and Lolium perenne . Here we report on the identification of specific E. festucae genes that control host infection. Deletion of setB , which encodes a homologue of the H3K36 histone methyltransferase Set2/KMT3, reduced histone H3K36 trimethylation and led to severe defects in colony growth and hyphal development. The E. festucae Δ clrD mutant, which lacks the gene encoding the homologue of the H3K9 methyltransferase KMT1, displays similar developmental defects. Both mutants are completely defective in their ability to infect L. perenne . Alleles that complement the culture and plant phenotypes of both mutants also complement the histone methylation defects. Co‐inoculation of either Δ setB or Δ clrD with the wild‐type strain enables these mutants to colonize the host. However, successful colonization by the mutants resulted in death or stunting of the host plant. Transcriptome analysis at the early infection stage identified four fungal candidate genes, three of which encode small‐secreted proteins, that are differentially regulated in these mutants compared to wild type. Deletion of crbA , which encodes a putative carbohydrate binding protein, resulted in significantly reduced host infection rates by E. festucae .

Interdisciplinary Research Collaborative Trains Students to See Through Turbulent Systems - Kristina Cammen; Gabriella Marafino; Sarah Burton; Jillian Dow; Emma Dullaert; Madalyn Jorge; Kate Macolini; Louise McGarry; Christopher Tremblay; Jessica Jansujwicz; Tora Johnson; Lauren Ross; et al. (Oceanography, 2021)
Despite the availability of interdisciplinary academic training programs, the practice of environmental science is often hampered by a lack of convergence across diverse disciplines. This gap is particularly salient in settings characterized by complex environmental issues, such as multiple-use coastal ecosystems. In response, we developed and implemented a training, research, and communication framework to provide undergraduates with an authentic operative experience working at the interface of interdisciplinary science and public decision-making within a case study of marine renewable energy. In our program, students gained hands-on experience with the scientific process and learned how to make information relevant, useful, and accessible to diverse stakeholder groups. Application of this framework demonstrates that the process of integrating data from biological (visual and acoustic monitoring of fish and marine mammals), physical (hydrodynamics), and social (local ecological knowledge) sciences can provide a more complete understanding of complex and turbulent ecosystems for better informed decision-making. We offer several recommendations to facilitate the adaptation and implementation of our interdisciplinary framework to diverse research contexts, with a focus on interdisciplinary training for the next generation of marine scientists.

Leveraging spatial dimensions of news media content analysis to explore place-based differences in natural resource issues - Kevin P. Duffy; Hugh C. Cipparone; Eileen S. Johnson; Laura N. Rickard; Kate Beard; Fernando Nascimento (Journal of Environmental Studies and Sciences, 2020)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Microtopography of fear memory consolidation and extinction retrieval within prefrontal cortex and amygdala - Angela Jacques; Nicholas Chaaya; Chiemi Hettiarachchi; Marie-Louise Carmody; Kate Beecher; Arnauld Belmer; Fatemeh Chehrehasa; Selena Bartlett; Andrew R. Battle; Luke R. Johnson (Psychopharmacology, 2019)

Effects of phosphorus starvation versus limitation on the marine cyanobacterium P rochlorococcus MED4 II : gene expression - Emily Nahas Reistetter; Kristen Krumhardt; Kate Callnan; Kathryn Roache‐Johnson; Jaclyn K. Saunders; Lisa R. Moore; Gabrielle Rocap (Environmental Microbiology, 2013)
Summary Phosphorus ( P ) availability drives niche differentiation in the most abundant phytoplankter in the oceans, the marine cyanobacterium P rochlorococcus . We compared the molecular response of P rochlorococcus strain MED4 to P starvation in batch culture to P ‐limited growth in chemostat culture. We also identified an outer membrane porin, PMM0709 , which may allow transport of organic phosphorous compounds, rather than phosphate as previously suggested. The expression of three P uptake genes, pstS , the high‐affinity phosphate‐binding component of the phosphate transporter, phoA , an alkaline phosphatase, and porin PMM0709 , were strongly upregulated (between 10‐ and 700‐fold) under both P starvation and limitation. pstS exhibits high basal expression under P ‐replete conditions and is likely necessary for P uptake regardless of P availability. A P ‐stress regulatory gene, ptrA , was upregulated in response to both P starvation and limitation although a second regulatory gene, phoB , was not. Elevated expression levels (> 10‐fold) of phoR , a P ‐sensing histidine kinase, were only observed under conditions of P limitation. We suggest P rochlorococcus in P ‐limited systems are physiologically distinct from cells subjected to abrupt P depletion. Detection of expression of both pstS and phoR in field populations will enable discernment of the present P status of P rochlorococcus in the oligotrophic oceans.

Effects of phosphorus starvation versus limitation on the marine cyanobacterium P rochlorococcus MED4 I : uptake physiology - Kristen M. Krumhardt; Kate Callnan; Kathryn Roache‐Johnson; Tammy Swett; Daniela Robinson; Emily Nahas Reistetter; Jaclyn K. Saunders; Gabrielle Rocap; Lisa R. Moore (Environmental Microbiology, 2013)
Summary Recent measurements of natural populations of the marine cyanobacterium P rochlorococcus indicate this numerically dominant phototroph assimilates phosphorus ( P ) at significant rates in P ‐limited oceanic regions. To better understand uptake capabilities of P rochlorococcus under different P stress conditions, uptake kinetic experiments were performed on P rochlorococcus MED4 grown in P ‐limited chemostats and batch cultures. Our results indicate that MED4 has a small cell‐specific V max but a high specific affinity (α P ) for P , making it competitive with other marine cyanobacteria at low P concentrations. Additionally, MED4 regulates its uptake kinetics in response to P stress by significantly increasing V max and α P for both inorganic and organic P ( PO 4 and ATP ). The Michaelis–Menten constant, K M , for PO 4 remained constant under different P stress conditions, whereas the K M for ATP was higher when cells were stressed for PO 4 , pointing to additional processes involved in uptake of ATP . MED4 cleaves the PO 4 moieties from ATP , likely with a 5′‐nucleotidase‐like enzyme rather than alkaline phosphatase. MED4 exhibited distinct physiological differences between cells under steady‐state P limitation versus those transitioning from P ‐replete to P ‐starved conditions. Thus, MED4 employs a variety of strategies to deal with changing P sources in the oceans and displays complexity in P stress acclimation and regulatory mechanisms.

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

Early Events of HIV-1 Infection: Can Signaling be the Next Therapeutic Target? - Kate L. Jones; Redmond P. Smyth; Cândida F. Pereira; Paul U. Cameron; Sharon R. Lewin; Anthony Jaworowski; Johnson Mak (Journal of Neuroimmune Pharmacology, 2011)

Social Value of Marine and Coastal Protected Areas in England and Wales - Kate Pike; David Johnson; Steve Fletcher; Paul Wright; Barbara Lee (Coastal Management, 2010)

Factors affecting hatching success of golden apple snail eggs: Effects of water immersion and cannibalism - Katherine C. Horn; Sally D. Johnson; Kate M. Boles; Anthony Moore; Evan Siemann; Christopher A. Gabler (Wetlands, 2008)

Detritus, trophic dynamics and biodiversity - John C. Moore; Eric L. Berlow; David C. Coleman; Peter C. de Ruiter; Quan Dong; Alan Hastings; Nancy Collins Johnson; Kevin S. McCann; Kim Melville; Peter J. Morin; Knute Nadelhoffer; Amy D. Rosemond; et al. (Ecology Letters, 2004)
Traditional approaches to the study of food webs emphasize the transfer of local primary productivity in the form of living plant organic matter across trophic levels. However, dead organic matter, or detritus, a common feature of most ecosystems plays a frequently overlooked role as a dynamic heterogeneous resource and habitat for many species. We develop an integrative framework for understanding the impact of detritus that emphasizes the ontogeny and heterogeneity of detritus and the various ways that explicit inclusion of detrital dynamics alters generalizations about the structure and functioning of food webs. Through its influences on food web composition and dynamics, detritus often increases system stability and persistence, having substantial effects on trophic structure and biodiversity. Inclusion of detrital heterogeneity in models of food web dynamics is an essential new direction for ecological research.

Mitochondrial DNA phylogeography of western lowland gorillas ( Gorilla gorilla gorilla ) - Stephen L. Clifford; Nicola M. Anthony; Mireille Bawe‐Johnson; Kate A. Abernethy; Caroline E. G. Tutin; Lee J. T. White; Magdelena Bermejo; Michelle L. Goldsmith; Kelley McFarland; Kathryn J. Jeffery; Michael W. Bruford; E. Jean Wickings (Molecular Ecology, 2004)
The geographical distribution of genetic variation within western lowland gorillas ( Gorilla gorilla gorilla ) was examined to clarify the population genetic structure and recent evolutionary history of this group. DNA was amplified from shed hair collected from sites across the range of the three traditionally recognized gorilla subspecies: western lowland ( G. g. gorilla ), eastern lowland ( G. g. graueri ) and mountain ( G. g. beringei ) gorillas. Nucleotide sequence variation was examined in the first hypervariable domain of the mitochondrial control region and was much higher in western lowland gorillas than in either of the other two subspecies. In addition to recapitulating the major evolutionary split between eastern and western lowland gorillas, phylogenetic analysis indicates a phylogeographical division within western lowland gorillas, one haplogroup comprising gorilla populations from eastern Nigeria through to southeast Cameroon and a second comprising all other western lowland gorillas. Within this second haplogroup, haplotypes appear to be partitioned geographically into three subgroups: (i) Equatorial Guinea, (ii) Central African Republic, and (iii) Gabon and adjacent Congo. There is also evidence of limited haplotype admixture in northeastern Gabon and southeast Cameroon. The phylogeographical patterns are broadly consistent with those predicted by current Pleistocene refuge hypotheses for the region and suggest that historical events have played an important role in shaping the population structure of this subspecies.

Microsatellite loci for studying clonal mixing, population structure and inbreeding in a social aphid, Pemphigus spyrothecae (Hemiptera: Pemphigidae) - PauL. C. D. Johnson; KatE. S. Llewellyn; William Amos (Molecular Ecology, 2000)

Effect of nitrogen and phosphorus addition on phenanthrene biodegradation in four soils - Carol R. Johnson; Kate M. Scow (Biodegradation, 1999)